2022
DOI: 10.1126/sciadv.add7063
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced reduction of Na + /H + exchanger isoform 1 promotes maladaptation of neuroplasticity and exacerbates depressive behaviors

Abstract: Major depression disorder (MDD) is a neuropsychiatric disorder characterized by abnormal neuronal activity in specific brain regions. A factor that is crucial in maintaining normal neuronal functioning is intracellular pH (pHi) homeostasis. In this study, we show that chronic stress, which induces depression-like behaviors in animal models, down-regulates the expression of the hippocampal Na + /H + exchanger isoform 1, NHE1, a major determinant of pHi in neurons.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…This effect was speculated to be due to increased excitotoxicity caused by ASIC1a activation, as acidic treatment induced an ASIC1a-dependent increase in intracellular Ca 2+ concentration in dendritic spines ( 82 ). Furthermore, a recent study showed that intracellular acidification in hippocampal neurons promotes dendritic spine loss and increases stress vulnerability in depression model rats ( 83 ). Therefore, extracellular and intracellular acidification may lead to spine impairments at the molecular and cellular levels that may be involved in psychiatric consequences.…”
Section: Discussionmentioning
confidence: 99%
“…This effect was speculated to be due to increased excitotoxicity caused by ASIC1a activation, as acidic treatment induced an ASIC1a-dependent increase in intracellular Ca 2+ concentration in dendritic spines ( 82 ). Furthermore, a recent study showed that intracellular acidification in hippocampal neurons promotes dendritic spine loss and increases stress vulnerability in depression model rats ( 83 ). Therefore, extracellular and intracellular acidification may lead to spine impairments at the molecular and cellular levels that may be involved in psychiatric consequences.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that brain lactate is an important regulator of tissue pH ( Prabakaran et al, 2004 ), although we cannot exclude the possibility that other factors, such as neuronal activity-regulated production of carbon dioxide, another metabolic acid, may also contribute to changes in brain pH ( Chesler, 2003 ; Zauner et al, 1995 ). Furthermore, the observed pH changes may be due to the dysregulation of neuronal ( Li et al, 2022 ; Pruett et al, 2023 ) and astroglial ( Theparambil et al, 2020 ) mechanisms of H + ion transport and buffering to regulate intracellular and extracellular pH homeostasis, which should be investigated in our model animals.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Lee et al also demonstrated that GluN3A knockout mice exhibited lower neuronal c-Fos expression and decreased phosphorylation levels of CaMKII in the olfactory bulb during olfactory discrimination tasks[69]. Li et al also reported that activity inhibition of CA1 pyramidal neurons could facilitate the depressive behaviors induced by stress[50]. On the other hand, a recent study by Su et al indicated that the increase CA1 neuronal activity, which induced by GluN2A inhibition, was essential for the rapid antidepressive effect of ketamine[22].…”
Section: Discussionmentioning
confidence: 99%
“…The structural and functional abnormalities of hippocampus have been recognized as important pathophysiological bases in depression and targets involved in the efficacy of antidepressant therapy[4547]. Extensive alterations in the number and morphology of neurons and synapses, as well as LTP and long-term depression (LTD) response in hippocampus are reported in depressive patients and animal models[4850]. The restoration of hippocampal abnormalities is consistent with the amelioration of depressive symptoms after chronic antidepressant treatment[15].…”
Section: Introductionmentioning
confidence: 99%